Experimental measurements of thermal conductivity and viscosity of ethylene glycol-based hybrid nanofluid with TiO2-CuO/C inclusions - Akilu, S. (Elsevier B.V., 2017)
In the present study, titanium oxide-copper oxide/carbon (TiO2-CuO/C) nanocomposite particles have been prepared via wet-mixing protocol. The nanocomposite was characterized by using scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), and X-ray powder diffraction (XRD). Subsequently, hybrid nanofluids were prepared by dispersing the nanocomposite in ethylene glycol (EG) as a base liquid. The thermal conductivity and viscosity of the nanofluids was measured in various volume concentrations (0.5, 1.0, 1.5, and 2) and temperatures ranging from 303.15 K to 333.15 K. The experimental results showed the sensitivity of thermal conductivity and viscosity with respect to variations in volume concentration and temperature. The maximum enhancement of thermal conductivity of TiO2-CuO/C hybrid nanofluid is 16.7, while the viscosity increased nearly by 80 at 2.0 volume concentration compared to base liquid at 313.4 K. The rheological analysis established that the hybrid nanofluid conforms to Newtonian classification of fluids. Finally, correlations for thermal conductivity and viscosity of nanocomposite based hybrid nanofluids were formulated which represent a satisfactory agreement between the experimental and calculated data with average absolute deviation ranging from 1 to 4. © 2017 Elsevier B.V.